The Effect of Audit Fees, Auditor Reputation, Auditor Rotation on Audit Quality in Food and Beverage Companies Listed on the BEI Periode 2019-2021 - Oktavia Nindita; Nirwana Nirwana (Journal of Finance and Business Digital, 2023)
This study aims to determine the effect of audit fees, auditor reputation, auditor rotation on audit quality in Food & Beverage Companies Listed on the Indonesia Stock Exchange. The data in this study were obtained from the company's financial statements accessed through the website. This research is a type of quantitative research using purposive sampling method. The samples in this study amounted to 14 Food & Beverage companies listed on the Indonesia Stock Exchange. The results of this study indicate that: the audit fee variable has a negative and significant effect, the auditor reputation variable has a negative and insignificant effect, and the auditor rotation variable has a negative and insignificant effect on audit quality.